Psychologically Deconstructing Socially-constructed Variables in Caribbean Identity Research - Arneaud, Mary Jane; Albada, Nicole (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
This conceptual paper illustrates how mediation analysis might psychologically deconstruct socially-constructed variables in Caribbean identity research. Psychosocial identity development status theory and research is reviewed. It is proposed that socio-demographic variables (i.e. age, class, ethnicity and gender) are constructed through social discourse. The implication is that social discourses should be examined to determine which psychological variables might best account for social group differences in identity status. Thus two regional discourses are explored for pertinent mediators of age, class, ethnicity and gender: the theory of the plantation economy and a Caribbean interpretation of race, class and ethnicity. Locus of control and cultural values emerge as pertinent psychological predictors for mediation analysis.